BMP15 c.-9C>G promoter sequence variant may contribute to the cause of non-syndromic premature ovarian failure (2014)
BMP15 has drawn particular attention in the pathophysiology of reproduction, as its mutations in mammalian species have been related to different reproductive phenotypes. In humans, BMP15 coding regions have been sequenced in large panels of women with premature ovarian failure (POF), but only some mutations have been definitely validated as causing the phenotype. A functional association between the BMP15 c.-9C>G promoter polymorphism and cause of POF have been reported. The aim of this study was to determine the potential functional effect of this sequence variant on specific BMP15 promoter transactivation disturbances. Bioinformatics was used to identify transcription factor binding sites located on the promoter region of BMP15. Reverse transcription polymerase chain reaction was used to study specific gene expression in ovarian tissue. Luciferase reporter assays were used to establish transactivation disturbances caused by the BMP15 c.-9C>G variant. The c.-9C>G variant was found to modify the PITX1 transcription factor binding site. PITX1 and BMP15 co-expressed in human and mouse ovarian tissue, and PITX1 transactivated both BMP15 promoter versions (-9C and -9G). It was found that the BMP15 c.-9G allele was related to BMP15 increased transcription, supporting c.-9C>G as a causal agent of POF. © 2014 Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.